Synthesis and Magnetic Property of Binuclear Copper(II) and Nickel(II) Complexes of Biprotic Bridging Ligand H2bspda - Chen, Hongji; Yang, Jun; Gao, Fangliang (Asian Journal of Chemistry, 2010)
Two binuclear complexes [MbspdaM(OAc)2·nH2O] (M = Cu(II), n = 1, 1; M = Ni(II), n = 2, 2, H2bspda = N,N'-bis(salicyidene)-5,6- phenanthrolinenediamine, have been prepared and characterized by element analysis, IR, 1H and 13C NMR, UV-Vis and EI-MS analysis. Magnetic measurements showed that both binuclear complexes exhibit anti-ferromagnetic interaction between the binuclear centers with the coupling coefficient value J/k = -4.02 K and corresponding g = 2.12 for 1 and J/k = -0.318 K and the corresponding g = 1.98 for 2.